HUBUNGAN POLA TIDUR DENGAN PERKEMBANGAN KOGNITIF PADA ANAK USIA SEKOLAH DI SDN 008 BATAM KOTA - Connie Raina Carissa; Sukma Sahreny; Widodo Pratama Putra (Universitas Batam, 2026)
ABSTRACT Background: Sleep patterns play a critical role in the cognitive development of school-aged children, particularly in the processes of memory consolidation and attention. This study aims to examine the relationship between sleep patterns and cognitive development among sixth-grade students at SDN 008 Batam Kota. Method: This analytical study with a cross-sectional design involved 63 students selected using a total sampling technique. Sleep patterns were assessed using the Pittsburgh Sleep Quality Index (PSQI), while cognitive development was evaluated using a questionnaire. Data analysis was conducted using the Spearman correlation test at a significance level of α = 0.05. Results: A total of 71.4% of respondents had good sleep patterns, and 82.5% demonstrated high-category cognitive development. The analysis indicated a significant positive relationship between sleep patterns and cognitive development (p = 0.004; r = 0.357). Conclusion: There is a significant relationship between sleep patterns and cognitive development in school-aged children. Good sleep quality contributes to the optimization of cognitive function. Keywords: Sleep Patterns, Cognitive Development, School-Age Children